Are Exercise Therapy Protocols For The Treatment of Hip-Related Pain Adequately Described? A Systematic Review of Intervention Descriptions - August Estberger; Joanne L Kemp; Kristian Thorborg; Anders Pålsson; Eva Ageberg (North American Sports Medicine Institute, 2023)
# Background Hip-related pain is an umbrella term encompassing pain from non-arthritic hip joint pathologies, such as femoroacetabular impingement syndrome, hip dysplasia, and labral tears. Exercise therapy is commonly recommended for these conditions, but the reporting completeness of these interventions is currently unclear. # Purpose The aim of this systematic review was to assess the reporting completeness of exercise therapy protocols for people with hip-related pain. # Study design Systematic review according to PRISMA guidelines. # Materials and Methods A systematic search was conducted, searching the MEDLINE, CINAHL, and Cochrane databases. The search results were independently screened by two researchers. Inclusion criteria were studies using exercise therapy in people with non-arthritic hip-related pain. Two independent researchers used the Cochrane risk of bias tool version 2 to analyze risk of bias, and the Consensus on Exercise Reporting Template (CERT) checklist and score (1-19) to synthesize reporting completeness. # Results Fifty-two studies used exercise therapy for hip-related pain, but only 23 were included in the synthesis as 29 studies had no description of the intervention. CERT scores ranged from 1 to 17 (median 12, IQR 5-15). The most well-described items were tailoring (87%), and the least well-described items were motivation strategies (9%) and starting level (13%). Studies used exercise therapy alone (n=13), or in combination with hip arthroscopy (n=10). # Conclusion Only 23 of 52 eligible studies reported sufficient details to be included in the CERT synthesis. The median CERT score was 12 (IQR 5-15), with no study reaching the maximum score of 19. Lack of reporting makes it difficult to replicate interventions in future research, and to draw conclusions on efficacy and dose-response to exercise therapy for hip-related pain. # Level of evidence Level 1, systematic review